فاعلية برنامج تدريبي لتنمية الكفايات التعليمية الأساسية لدى معلمات رياض الأطنة عمان - Sawafi Jokha Mohammed Saleem
The study aims at identifying the degree of practicing the educational competencies among kindergarten teachers and to test whether there are differences in the availability of these competencies are affected with the variables (academic qualification, experience, training courses) and to measure the effectiveness of the training program in developing these competencies.The researcher used two approaches in the study: descriptive approach, and experimental approch and two tools were applied: A note card, A training program. The observation card was applied to a sample of (610) teachers from which (10) were chosen to represent the experimental. The study found the following results: -The teachers practice the competencies (planning, evaluation, the educational performance, classroom management and interaction with children, use of teaching aids) within (medium) degree while practicing competencies (organizing the educational environment and personal competencies) with a high degree. - the degree of availability of competencies among teachers in all fields varies according to the qualification of the teacher in favor of Bachelor degree. -The degree of availability of competencies does not vary according to experience. د - The degree of availability of competencies in six fields, vary according to training courses except the field (educational environment) that does not vary accordingly. -There are statistically significant differences in the availability of the competencies due to the academic qualification with experience. -There are statistically significant differences in the degree of the competencies practice in post training measurement between the experimental and controlled groups in favor of the experimental group due to the training program.